ANALISIS KELAYAKAN USAHA UMKM "ACHYO PAWON REMPAH" DITINJAU DARI ASPEK FINANSIAL SERTA BUSINESS MODEL CANVAS (BMC) - Aritia Nashwa Hanyunari, (2023)
UMKM Achyo Pawon Rempah is one of the UMKM in the food and beverage industry, producing herbal drinks in bottles. The owner has aspirations to develop his business by trying to expand sales and marketing to join the modern market. The owner wants to know what strategies can be implemented so that the business can develop and run according to the target. The purpose of this research is to find out the strategy and feasibility in financial terms which are calculated using NPV, PP, ROA, ROI, ROE and PI of 3 conditions for prices following benchmarks, namely lowest price, selling price and highest price and analyze the sensitivity of these conditions from the calculation of the break even point. The research also using business model canvas to explain and design a business strategy based on the results of the interviews. The results of data processing, for the lowest price condition cannot be used because it has a negative cash flow accumulation and the selling price condition is selected because this price can be considered competitive in the benchmarks.